Circ_0001490/miR-579-3p/FSTL1 axis modulates the survival of mycobacteria and the viability, apoptosis and inflammatory response in Mycobacterium tuberculosis-infected macrophages. (December 2021) - Deng, Qun; Huang, Jian; Yan, Jinjin; Mao, Erning; Chen, HuiJuan; Wang, Caiwen
Abstract: Background: Macrophages play an important role in the host immune response against mycobacterial infection, and this process is regulated by various factors, including circular RNAs (circRNAs). We intended to explore the role of circ_0001490 in tuberculosis (TB) using Mycobacterium tuberculosis (M.tb)-infected THP-1 macrophages. Methods: Real-time quantitative polymerase chain reaction (RT-qPCR) and Western blot assay were conducted to measure RNA and protein expression, respectively. 3-(4, 5-Dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide (MTT) assay was conducted to analyze the viability of THP-1 macrophages. Flow cytometry was performed to analyze the apoptosis rate of THP-1 macrophages. Enzyme-linked immunosorbent assay (ELISA) was conducted to assess the release of inflammatory cytokines. Colony-forming unit (CFU) assay was conducted to analyze the survival of M.tb in THP-1 macrophages. Intermolecular target interaction was verified by dual-luciferase reporter assay and RNA immunoprecipitation (RIP) assay. Results: Circ_0001490 expression was down-regulated in the serum samples of TB patients and M.tb-infected THP-1 macrophages. Circ_0001490 overexpression suppressed M.tb survival and promoted the viability and inflammatory response of THP-1 macrophages. Circ_0001490 interacted with microRNA-579-3p (miR-579-3p), and circ_0001490 overexpression-induced protective effects in M.tb-infected THP-1 macrophages were largely overturned by the overexpression of miR-579-3p. miR-579-3p interacted with the 3′ untranslated region (3′UTR) of follistatin-like protein 1 (FSTL1). FSTL1 silencing largely overturned miR-579-3p knockdown-induced effects in M.tb-infected THP-1 macrophages. Circ_0001490 acted as miR-579-3p sponge to up-regulate FSTL1 in THP-1 macrophages. Conclusion: In conclusion, our results demonstrated that circ_0001490 suppressed M.tb survival and promoted the viability and inflammatory response of M.tb-infected THP-1 macrophages partly by regulating miR-579-3p/FSTL1 axis.